Structural Changes and Evolution of Peptides During Chill Storage of Pork - Zou, Xiaoyu; He, Jing; Zhao, Di; Zhang, Min; Xie, Yunting; Dai, Chen; Wang, Chong; Li, Chunbao (Frontiers in Nutrition, 2020)
In this work, we investigated changes in protein structures in vacuum-packed pork during chill storage and its impact on in vitro protein digestion. Longissimus dorsi muscles were vacuum packed and stored at 4°C for 3 days. Samples were subjected to Raman spectroscopy, in vitro digestion and Nano LC-LTQ-Orbitrap XL MS/MS. The 3 d samples had lower α-helix content, but higher β-sheet, β-turn and random coil contents than the 0 d samples (P < 0.05). SDS-PAGE revealed significant protein degradation in the 3 d samples and the differences in digested products across storage time. Proteome analysis indicated that the 3 d samples had the higher susceptibility to digestion. Increasing protein digestibility was mainly attributed to the degradation of myofibrillar proteins. Thus, exposure of more enzymatic sites in loose protein structure during chill storage could increase protein degradation in meat.